Preparedness of health care systems for Ebola outbreak response in Kasese and Rubirizi districts, Western Uganda - Michael Kibuule; Deogratias Sekimpi; Aggrey Agaba; Abdullah Ali Halage; Michael Jonga; Leonard Manirakiza; Catherine Kansiime; Dominic Travis; Katharine Pelican; Innocent B. Rwego (BMC, 2021)
Abstract Background The level of preparedness of the health care workers, the health facility and the entire health system determines the magnitude of the impact of an Ebola Virus Disease (EVD) outbreak as demonstrated by the West African Ebola outbreak. The objective of the study was to assess preparedness of the health care facilities and identify appropriate preparedness measures for Ebola outbreak response in Kasese and Rubirizi districts in western Uganda. Methods A cross sectional descriptive study was conducted by interviewing 189 health care workers using a structured questionnaire and visits to 22 health facilities to determine the level of health care system preparedness to EVD outbreak. District level infrastructure capabilities, existence of health facility logistics and supplies, and health care workers' knowledge of EVD was assessed. EVD Preparedness was assessed on infrastructure and logistical capabilities and the level of knowledge of an individual health work about the etiology, control and prevention of EVD. Results Twelve out of the 22 of the health facilities, especially health center III's and IV's, did not have a line budget to respond to EVD when there was a threat of EVD in a nearby country. The majority (n = 13) of the facilities did not have the following: case definition books, rapid response teams and/or committees, burial teams, and simulation drills. There were no personal protective equipment that could be used within 8 h in case of an EVD outbreak in fourteen of the 22 health facilities. All facilities did not have Viral Hemorrhagic Fever (VHF) incident management centers, isolation units, guidelines for burial, and one-meter distance between a health care worker and a patient during triage. Overall, 54% (n = 102) of health care workers (HCWs) did not know the incubation period of EVD. HCWs who had tertiary education (aOR = 5.79; CI = 1.79-18.70; p = 0.003), and were Christian (aOR = 10.47; CI = 1.94-56.4; p = 0.006) were more likely to know about the biology, incubation period, causes and prevention of EVD. Conclusions Feedback on the level of preparedness for the rural districts helps inform strategies for building capacity of these health centers in terms of infrastructure, logistics and improving knowledge of health care workers.